PENGALAMAN HIDUP SELF-MANAGEMENT PADA PASIEN GAGAL GINJAL KRONIK DI BANTEN - Fatimah, Marzelisa Claudia; Ernawati, Eka; Lukmanulhakim, Lukmanulhakim (Coping: Community of Publishing in Nursing; Vol 10 No 2 (2022): April 2022, 2022)
Patients with chronic kidney failure are expected to be able to carry out self-management in terms to fluid management, diet, vascular access, treatment regimens, and activity patterns are still obstacles. Self-management is an activity to change bad habits by learning to adapt to changes in their health. Patients with chronic kidney disease undergoing hemodialysis require good self-management. With a change in the patient's life, the phenomenon of self-management is unique. The purpose of this study was to describe the self-management of chronic kidney disease patients undergoing hemodialysis in the Banten region. This study uses a qualitative method with a phenomenological approach. Data collection by in-depth interview. Participants were taken using purposive sampling totaling six participants. The results of the study found two new themes: 1) non-compliance with fluid diet and diet, 2) testament can be submitted by patients with chronic kidney disease.